Methodology for an ecological solution of subsurface flow constructed wetlands used in the treatment of greywater. Issue 12 (18th November 2022) - Anigrou, Yassine; Bahlami, Ahmed; El Khlifi, Mohamed
Abstract: Hammams or public baths continue to consume substantial quantities of drinking water up to 120 m 3 /day and discharge equivalent quantities of greywater. These hammams thus become an important source of this greywater, which can be easily treated using constructed wetlands (CWs). In this context, the present study proposes to practitioners a general method for sizing subsurface flow (SSF) CWs for the treatment of greywater discharged from hammams. It is oriented to simple applications such as irrigation, car washing and toilet flushing. Due to the complexity of quantifying the evapotranspiration ( ET ) of the treated water at the CWs, a practical and flexible method is presented here to calculate ET . In the end, a case study of a Moroccan hammam has been treated and discussed. It provides the designers of SSF CWs with a concrete example of the application of the proposed methodology. HIGHLIGHTS: Design method for constructed wetlands with the subsurface flow for greywater treatment. Method for calculating water evapotranspiration in constructed wetlands with the subsurface flow. Practical reference for designers of constructed wetlands with the subsurface flow. Contribution to facilitate the implementation of eco-systems for water reuse for non-potable purposes, thus reducing the inappropriate demand for treated drinking water.